The effects of film thickness on the optical properties of TiO2–SnO2compound thin films - Sönmezoğlu, Savaş; Arslan, Aysun; Serin, Tülay; Serin, Necmi (IOP Publishing, 2011)
In this work, TiO2?SnO2 compound thin films was synthesized by the sol?gel technique, and the effects of film thickness on the optical and structural properties of these thin films were investigated. Optical constants such as the refractive index, extinction coefficient, dielectric constant and third-order optical nonlinear susceptibility were determined from the measured transmittance spectra in the wavelength range 300?1500?nm using the envelope method. Meanwhile, the dispersion behavior of the refractive index was studied in terms of the single-oscillator Wemple?DiDomenico (W?D) model, and the physical parameters of the refractive index dispersion parameter and the dispersion energy were found. Furthermore, the optical band gap values were calculated by the W?D model and the Tauc model, respectively. It is observed that the values obtained from the W?D model are in quite good agreement with those determined from the Tauc model. Important changes in optical and dielectric constants were observed by means of variation in film thickness. To examine the structure of the thin films, x-ray diffraction (XRD) methods were used. Combined with XRD analysis, the observed variations in both the refractive index and optical band gap are directly correlated with the structural evolution of the composite TiO2?SnO2 thin films. The most significant results of the present study are that the thickness of the film can be used to modify the optical, structural and dielectric properties of TiO2?SnO2 thin films.